Profile of maternal near miss and determinant factors in a Teaching Hospital, Southwestern Nigeria - Aduloju, Olusola P.; Aduloju, Tolulope; Ipinnimo, Oluwadare M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal near miss (MNM) concept is becoming a tool for the assessment of severe maternal morbidity. The study examined the profile of MNM cases and their determinant factors. Methods: A cross-sectional study of pregnant women with near miss cases and maternal death using the WHO criteria between 1st January 2015 and 31st December 2016. Relevant data were collected with using a structured data form, analyzed using SPSS version 22 and logistic regression was done to determine factors associated with MNM. Results: The MNM incidence ratio was 17.4/1000 live births with overall mortality index of 17.5%. Hemorrhage (39.4%) was the commonest cause of MNM while uterine rupture (42.8%) was the most common cause of maternal death. Also, uterine rupture had the highest mortality index of 33.3%. Older age group, low education, rural dwellers and unbooked status of women were the significant determinants of MNM, p <0.05. The overall maternal death to near miss ratio was 1:4.7. The worst perinatal outcome occurred in women who suffered maternal death. Conclusions: The study showed suboptimal level of care for women with life threatening conditions. There is a need to develop evidence-based protocol for their management and provision of high dependency unit.